Effect of an informational guideline application on lifestyle among primigravid (Latakia University Journal -Medical Sciences Series, 2023)
A healthy lifestyle aim to reduce the risk factors that leading to pregnancy and childbirth problems, and to raise public health awareness about the positive impacts of healthy nutrition, physical activity, family support, and self-realization on the health of the primigravid. Therefore, the current experimental study aim to find out the effect of applying an informational guide on the lifestyle of the primigravid, in a sample of 100 primigravid women who were chosen in an appropriate manner from the women attending the women's clinic in Tishreen University Hospital, and they were randomly divided equally into two groups: an experimental one which the informational guide was applied and control group a female officer left for routine care in the women's clinic, and the researcher used a healthy life support scheme to collect data. The study showed effectiveness of applying an information guide about the healthy lifestyle of the primigravid in improving their lifestyle in all the studied dimensions (self-realization, health care, exercise, nutrition, support for the surrounding people, management and treatment of pressures), and the self-realization dimension came in the first place after applying the informational guide and the aerobic exercise dimension in the last order. The study recommended the necessity of adopting the informational guide applied in the study as an educational and guiding method for women who are obese, and adopting practical training for physical exercises during pregnancy